The negative effects of social media on the social identity of adolescents from the perspective of social work. Issue 2 (February 2021) - Elsayed, Walaa
Abstract: The aim of this study was to understand the social identity levels of adolescents and to analyze the negative effects of social media on their social identity from the perspective of social work. The researcher used a descriptive-analytical technique in this study. The study's sample consisted of 200 adolescents (male and female) in the secondary stage at age group (15–18 years). The researcher designed a questionnaire based on the four main levels of James Marcia's theory of social identity. The results showed a variety of negative effects of social media on the social identity of adolescents in terms of "achievement - postponement - closure - dispersion", this requires taking serious measures from the family, the school, and other institutions to care for the family and the child to strengthen how to face these risks to protect the identity of adolescents from violating their privacy and negatively affecting their intellectual principles. Abstract : Negative Effects; Social Media; Social Identity; Adolescents; Social Work.